2022
DOI: 10.1371/journal.pone.0263159
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state electroencephalography based deep-learning for the detection of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is one of the most serious and challenging neurodegenerative disorders to diagnose. Clinical diagnosis on observing motor symptoms is the gold standard, yet by this point nerve cells are degenerated resulting in a lower efficacy of therapeutic treatments. In this study, we introduce a deep-learning approach based on a recently-proposed 20-Layer Convolutional Neural Network (CNN) applied on the visual realization of the Wavelet domain of a resting-state EEG. The proposed approach was ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…E.g., our accuracy is about 14.12% higher than the linear-predictive-coding EEG algorithm proposed by Anjum et al (2020) , and about 10.52% higher than the Hjorth parameter and the gradient boosting decision tree algorithm proposed by Lee et al (2022) . For the UC San Diego dataset (15 PD patients and 16 controls), the classification performance (accuracy, sensitivity, specificity, and AUC are above 93% in γ band) of our proposed MCNN model is comparable, although not the highest, compared to other related studies ( Khare et al, 2021a , b ; Loh et al, 2021 ; Shaban, 2021 ; Shaban and Amara, 2022 ). Some previous work can achieve close to 100% accuracy ( Barua et al, 2021 ; Khare et al, 2021b ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…E.g., our accuracy is about 14.12% higher than the linear-predictive-coding EEG algorithm proposed by Anjum et al (2020) , and about 10.52% higher than the Hjorth parameter and the gradient boosting decision tree algorithm proposed by Lee et al (2022) . For the UC San Diego dataset (15 PD patients and 16 controls), the classification performance (accuracy, sensitivity, specificity, and AUC are above 93% in γ band) of our proposed MCNN model is comparable, although not the highest, compared to other related studies ( Khare et al, 2021a , b ; Loh et al, 2021 ; Shaban, 2021 ; Shaban and Amara, 2022 ). Some previous work can achieve close to 100% accuracy ( Barua et al, 2021 ; Khare et al, 2021b ).…”
Section: Discussionmentioning
confidence: 64%
“… Barua et al (2021) achieved 99.93% and 100% classification accuracy for HC vs. PD_OFF and HC vs. PD_ON using the proposed novel aspirin pattern, respectively. Shaban and Amara (2022) used a continuous wavelet-based deep learning method to obtain a high accuracy of 99.9% for PD detection. Although these studies achieved slightly higher accuracy than our proposed model, their methods were only validated on a single dataset and did not generalize to other datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, external neural interfaces of the EEG type are associated with a much lower risk for the user and can be used to noninvasively monitor brain states (including cognitive stress load and sleep patterns) and brain health, opening the possibility, for example, to diagnose epilepsy, as well as potentially screen for and achieve an early diagnosis of some of the neurodegenerative diseases. In addition, noninvasive neural interfaces open the path toward all nonclinical hands-free control of autonomous external devices by harnessing the brain signals, including robotics, bionic prosthetics, neurogaming, consumer electronics, as well as autonomous vehicles. The external devices can be controlled by the interpretation of human intention via detecting the cortical electrical activity, eye movement, and muscle movement through EEG, electrooculography (EOG), and electromyography (EMG), respectively, which all rely on noninvasive sensors. ,, The foundation concept of interconnecting external devices directly with brain signals was demonstrated by Hans Berger in 1929 by developing the first-generation EEG device using two channels with metallic needle electrodes to enable the noninvasive recording of neuroelectrical brain signals . The first scientific study on volitional control of human brain oscillation was reported by Kamiya et al in 1969, where the change of “alpha waves” (neural oscillations in the frequency range of 8–13 Hz) on continuous sensory feedback using EEG channels at the C 4 -O 2 , C z -A 2 positions had been demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies report very high accuracies above 98%. [5 - 12] However, the methods employed in these articles may suffer from the limitation of information-leakage between the training and testing data [6]. This limitation can lead to large overestimation of classification ability on unseen, real-world data.…”
Section: Introductionmentioning
confidence: 99%